Use of personal protective equipment to care for patients with COVID-19: scoping review - Gracielle Pereira Aires Garcia; Isabela Fernanda Larios Fracarolli; Heloisa Ehmke Cardoso dos Santos; Virgínia Ramos dos Santos Souza; Camila Maria Cenzi; Maria Helena Palucci Marziale (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To summarize the knowledge about recommendations for the use of personal protective equipment necessary for the provision of care by health professionals to patients suspected or infected by the new coronavirus. Method Scoping review with search for primary studies, reviews and preprints articles in English, Portuguese and Spanish, in the last 20 years on the bases WOS/ISI, SCOPUS, MEDLINE/PuBMed, CINAHL, LILACS and SciELO. Unpublished studies in journals were surveyed on bioRxiv and SciELO preprints. Results 23 studies were eligible. Experiences with coronavirus prior to SARS-CoV-2 revealed that the equipment was an essential barrier in preventing transmission and followed the recommendations for standard precautions, contact, droplet and aerosol. In 13 (57%) studies, this equipment complied international recommendations and in 10 (45%) local recommendations. Conclusion The personal protective equipment used does not follow global standardization according to type, quality and adequate provision, exposing these professionals to the risk of contamination.